PENERAPAN ASAS LEX SPECIALIS SYSTEMATISCHE DEROGAT LEGI GENERALI DALAM PENANGANAN KASUS KORUPSI PENYALAHGUNAAN WEWENANG DALAM PEMBERIAN IZIN TAMBANG NIKEL (STUDI PUTUSAN NO.118/PID.SUS-TPK/2023/PN JKT PST) - Tambunan, Stephy Anggi Eliza; Mulyadi, Mahmud; Lubis, Rafiqoh (Jurnal Hukum Statuta, 2025)
The high strategic value of the mining sector makes it vulnerable to corrupt practices, particularly in the process of mining permit issuance. One case that reflects this issue is District Court Decision No. 118/Pid.Sus-TPK/2023/PN. Jkt Pst, the issues addressed in this research include the regulation of criminal law in the mining sector under Law No. 3 of 2020 on the Amendment to Law No. 4 of 2009, the relationship between provisions on the abuse of authority in the Law on the Eradiction of Corruption and the Law on Mineral and Coal Mining in the application of this principle in the handling of corruption cases involving abuse of authority in the issuance of mining permits based on is District Court Decision No. 118/Pid.Sus-TPK/2023/PN Jkt Pst. This research uses normative legal research methods with a statutory approach and case approach. Based on the findings, it is revealed that spesific provisions previously regu;ated under the Mineral and Coal Mining Law concerning permit issuance were removed in the amandments introduced through Law No. 3 of 2020. As a results, the lex specialis systematische derogat legi generali  principle cannot be applied to the Corruptioin Law because there are no longer any special provisions remaining in the Mineral and Coal Mining Law that can serve as a basis for comparison. Thus, the legal resolution in this decision is appropriate, and the principle of lex specialis systematische derogat legi generali cannot be applied in this case.